Optimizing Germanium-Selective Functionalization on Patterned SiGe Substrates with Thiol-Based Molecules: The Critical Role of Oxygen-Free Conditions - Alessia Arrigoni; Federico Turco; Benedetta Maria Squeo; Sonia Freddi; Monica Bollani; Tersilla Virgili; Andrea Chiappini; Laura Pasquardini; Mariacecilia Pasini (Chemistry Proceedings)
Germanium offers attractive optical properties despite being an indirect bandgap semiconductor, and new Ge-based devices are being optimized for sensing and photonics applications. In particular, considering the use of Ge as a sensor, improving its selectivity via organic grafting offers new alternatives that are still under investigation. In this work, we focus on the selective functionalization of germanium in SiGe-patterned alloys using a custom thiol-based luminescent molecule, namely 6-[2,7-bis[5-(5-hexyl-2-thienyl)-2-thienyl]-9-(6-sulfanylhexyl)fluoren-9-yl]hexane-1-thiol. The process selectively targets regions with Ge, while leaving Si-rich areas uncovered. Moreover, this study emphasizes the importance of an oxygen-free environment, as performing the functionalization in an inert atmosphere significantly improves surface coverage.